Work-life balance in Europe: the role of job quality (Basingstoke, 2011)
"This volume addresses tensions between work and private life by focusing on job quality, job security, working conditions and time-use patterns of individuals and households on the one hand, and the institutional context, such as family policy institutions, and other country characteristics on the other. The length of time spent on work, job characteristics, and working conditions in general to a large extent influences the degree to which people are able to combine work and other important life domains, such as family, care and social life. Jobs which facilitate a more favourable combination of people's work and personal lives lead to a better work-life balance and higher life satisfaction, which in turn might increase identification and satisfaction with one's job and work productivity. This book explores which work-related demands and work-related resources interfere with, or facilitate, the work-life interface, and how these factors interact with the institutional settings."